Studies on Interrelationsidp of Woody Vegetation Density and Soil Characteristics along an Altitudinal Gradient in a Montane forest of Garhwal Himalayas - Rawat, R. S. (Indian Forester, 2005)
In the present study density of woody vegetation and soil characteristics were studied along an altitudinal gradient from 1,700 to 2,100 m above msl in a mountain flank of Garhwal Himalaya,. Maximum total tree density (density of tree, sapling and seedling) was recorded for the upper slope followed by middle and lower slopes respectively; whereas in case of shrub maximum density was recorded for lower slope followed by middle and upper slope respectively. Results of soil pH, organic carbon and potassium were found to be statistically significant at 5 per cent level of significance; where organic carbon and potassium were positively correlated and soil pH showed negative correlation with the altitudinal gradient. However, phosphorus content showed non-significant correlation.